Quantitative Analysis of the Supraorbital, Transorbital Microscopic, and Transorbital Neuroendoscopic Approaches to the Anterior Skull Base and Paramedian Vasculature - Houlihan, Lena Mary; Loymak, Thanapong; Abramov, Irakliy; Jubran, Jubran H.; Staudinger Knoll, Ann J.; O'Sullivan, Michael G. J.; Lawton, Michael T.; Preul, Mark C. (Journal of Neurological Surgery Part B: Skull Base, 2024)
Objectives Our objective was to compare transorbital neuroendoscopic surgery (TONES) with open craniotomy and analyze the effect of visualization technology on surgical freedom.Design Anatomic dissections included supraorbital craniotomy (SOC), transorbital microscopic surgery (TMS), and TONES.Setting The study was performed in a neurosurgical anatomy laboratory.Participants Neurosurgeons dissecting cadaveric specimens were included in the study.Main Outcome Measures Morphometric analysis of cranial nerve (CN) accessible lengths, frontal lobe base area of exposure, and craniocaudal and mediolateral angle of attack and volume of surgical freedom (VSF) of the paraclinoid internal carotid artery (ICA), terminal ICA, and anterior communicating artery (ACoA).Results The mean (standard deviation [SD]) frontal lobe base parenchymal exposures for SOC, TMS, and TONES were 955.4 (261.7) mm2, 846.2 (249.9) mm2, and 944.7 (158.8) mm2, respectively. Access to distal vasculature was hindered when using TMS and TONES. Multivariate analysis estimated that accessing the paraclinoid ICA with SOC would provide an 11.2- mm3 increase in normalized volume (NV) compared with transorbital corridors (p < 0.001). There was no difference between the three approaches for ipsilateral terminal ICA VSF (p = 0.71). Compared with TONES, TMS provided more access to the terminal ICA. For the ACoA, SOC produced the greatest access corridor maneuverability (mean [SD] NV: 15.6 [5.6] mm3 for SOC, 13.7 [4.4] mm3 for TMS, and 7.2 [3.5] mm3 for TONES; p = 0.01).Conclusion SOC provides superior surgical freedom for targets that require more lateral maneuverability, but the transorbital corridor is an option for accessing the frontal lobe base and terminal ICA. Instrument freedom differs quantifiably between the microscope and endoscope. A combined visualization strategy is optimal for the transorbital corridor.
Keywords: anterior skull base; neuroanatomical quantitation; supraorbital craniotomy; TMS; TONES